2008
DOI: 10.1021/jf802138y
|View full text |Cite
|
Sign up to set email alerts
|

Plasma and Tissue Depletion of Florfenicol and Florfenicol-amine in Chickens

Abstract: Chickens were used to investigate plasma disposition of florfenicol after single intravenous (i.v.) and oral dose (20 mg kg-1 body weight) and to study residue depletion of florfenicol and its major metabolite florfenicol-amine after multiple oral doses (40 mg kg-1 body weight, daily for 3 days). Plasma and tissue samples were analyzed using a high-performance liquid chromatography (HPLC) method. After i.v. and oral administration, plasma concentration-time curves were best described by a two-compartment open … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
57
0
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(70 citation statements)
references
References 34 publications
7
57
0
6
Order By: Relevance
“…The C max was 9.02 ± 0.68 and 9.20 ± 0.77 μg/ml achieved at 01.02 ± 0.13 and 01.05 ± 0.30h (t max ) for Flonicol ® and Veterin ® 10%, respectively. The C max obtained in the present study were similar to those reported previously in chickens at a dose level of 20mg/kg bw (10.23 ± 1.67 μg/ml) [31], higher than those reported in chickens at a dose level of 30 mg/kg bw (5.82 ± 2.43 and 3.20 ± 0.20 μg/ml) [15,24] similar to those reported in E. coli infected broiler chickens (7.9 ± 3.00 μg/ml) [17] and lower than those reported in turkeys (12.25 ± 2.62 μg/ml) [7]. The observed t max was similar to those reported in healthy broiler chickens (1.05 ± 0.07h and 1.35 ± 0.43h) [15,16] and E. coli infected broiler chickens (1.1 ± 0.43h) [5] but shorter than those reported in turkeys (2.0 ± 1.22h) [7].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The C max was 9.02 ± 0.68 and 9.20 ± 0.77 μg/ml achieved at 01.02 ± 0.13 and 01.05 ± 0.30h (t max ) for Flonicol ® and Veterin ® 10%, respectively. The C max obtained in the present study were similar to those reported previously in chickens at a dose level of 20mg/kg bw (10.23 ± 1.67 μg/ml) [31], higher than those reported in chickens at a dose level of 30 mg/kg bw (5.82 ± 2.43 and 3.20 ± 0.20 μg/ml) [15,24] similar to those reported in E. coli infected broiler chickens (7.9 ± 3.00 μg/ml) [17] and lower than those reported in turkeys (12.25 ± 2.62 μg/ml) [7]. The observed t max was similar to those reported in healthy broiler chickens (1.05 ± 0.07h and 1.35 ± 0.43h) [15,16] and E. coli infected broiler chickens (1.1 ± 0.43h) [5] but shorter than those reported in turkeys (2.0 ± 1.22h) [7].…”
Section: Discussionsupporting
confidence: 91%
“…The t 1//2β was similar to those data reported in chickens (1.78 ± 0.19) [15] and E.coli infected broiler chickens (1.73 ± 0.25h) [17] and shorter than those reported in turkeys (3.76h) [7] and chickens in other studies (8.34 +/-0.64h and 2.25 ± 0.53h) [13,31]. Differences between studies in chickens could be attributable to differences in the pharmacokinetic analysis (fitting to 1-versus 2-compartment models versus noncompartmental models).…”
Section: Discussionsupporting
confidence: 89%
“…The pharmacokinetic profile of florfenicol has been described in chickens (Shen et al ., ; Anadon et al ., ), turkeys (Switala et al ., ), pigs (Li et al ., ; Liu et al ., ), dogs (Park et al ., ), rabbits (Koc et al ., ) and sheep (Lane et al ., ). Florfenicol pharmacokinetics has also been reported in adult cattle (Bretzlaff et al ., ; Varma et al ., ; Soback et al ., ) and calves (Varma et al ., ; Adams et al ., ; Lobell et al ., ; De Craene et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…In the most cases pharmacokinetics and the tissue depletion of antibiotics have been studied in healthy animals (Anadón et al 2008;El-Gendi et al 2010;Anadón et al 2011;Anadón et al 2012;Li et al 2013), and influence of infection on the tissue pharmacokinetics is studied very rarely (AgersØ and Friis 1998;Ding et al 2013). …”
Section: Discussionmentioning
confidence: 99%